KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU - Rohmawati , Zulfa (UNISAN JURNAL, 2024)
The author conducted research at terms of the school system which is quite structured, the infrastructure facilities are adequate according to what is needed in the learning process. This research uses a qualitative approach, namely field research, namely research that examines facts and problems in the field, or research that solves the problem using empirical data. The method used in collecting data with the method of observation, interviews and documentation. The results of this study are to analyze financing management in improving the quality of graduates by carrying out the functions of 3 important stages including: financial planning (budgeting), implementation (accounting), and assessment (auditing). The principal’s leadership role in improving teacher performance includes: Motivating teacher performance, coaching discipline, Giving awards, Providing consultations, Conducting class visits.